1995
DOI: 10.1007/bf00311445
|View full text |Cite
|
Sign up to set email alerts
|

The use of an ileostomy connector to diminish the frequency of defecation prior to ileostomy closure in patients with a pelvic pouch

Abstract: A new method for allowing stool passage into the pelvic pouch before ileostomy closure to verify the defecation state and diminish stool frequency is reported herein. This was accomplished by fitting an ileostomy connector connecting the proximal and distal openings of the diverting loop stoma. The ileostomy connector was initially in place for 6 h a day, the length of time being gradually increased until it was able to be left in for 24 h a day over a 3-month period. The calculated daily frequency of stools d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…39 The aims of this technique were to predict postclosure complications, using a simple reversible device and to reduce the frequency of defecation after closure. A custom-designed connector was inserted in a single patient, 12 weeks after ileostomy formation, until closure 3 months later.…”
Section: Discussionmentioning
confidence: 99%
“…39 The aims of this technique were to predict postclosure complications, using a simple reversible device and to reduce the frequency of defecation after closure. A custom-designed connector was inserted in a single patient, 12 weeks after ileostomy formation, until closure 3 months later.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two comparative studies did not observe a difference between the intervention and the control group 5 days [42] or 7 days postoperatively [43]. In the case report of a patient with an ileoanal pouch who underwent bowel stimulation with an ileostomy connector [40], the daily frequency of stools within the first 24 h after ileostomy closure was 6.5 times and therefore slightly less than in the comparative studies. Two case reports reported results regarding the onset of intestinal peristalsis [37,41], which were similar.…”
Section: Other Functional Outcomesmentioning
confidence: 85%
“…1). We included seven published studies from three bibliographic databases [37][38][39][40][41][42][43] and an ongoing study identified from ClinicalTrials.gov [44], for which the corresponding author provided results of an interim analysis that had been presented at the 22nd National Meeting of the Spanish Association Foundation of Coloproctology in Bilbao, Spain on 9 May 2018.…”
Section: Search and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…GI side effects were reported in association with CR in some studies, including abdominal discomfort, diarrhea, constipation, nausea, and vomiting, which were generally controlled sufficiently to enable reinfusion to be continued. 10,20,23,29,36,41,42 However, it was not clear whether these effects were directly related to CR or the underlying etiology that resulted in DES or EAF formation, or both. One article noted that extremely rapid or bolus reinfusion may contribute to these symptoms.…”
Section: Adverse Events and Mortalitymentioning
confidence: 99%